Calculation of two-frequency induction systems - tools for external magnetic-pulse straightening of automobile bodies - Далека, Василий Фомич; Бондаренко, Александр Юрьевич; Степанов, Александр Александрович (Technology audit and production reserves, 2014)
The paper considers the issue related to the improvement of the existing methods of calculating a tool for external magnetic-pulse straightening of auto body parts. The purpose of the research is to calculate the field density ratio, excited in two-frequency induction systems, i.e. tools for external magnetic-pulse straightening of dents in auto body metal coatings. The calculated ratios for the field density, excited in two-frequency induction systems, i.e. the tools for external magnetic-pulse straightening of dents in auto body metal coatings are obtained in the paper. This allows solving the problems related to the space-time distribution of the resulting magnetic field strength in sheet metal dents, i.e. improving induction system efficiency that is the main direction in designing special devices. The research results can be used by scientists and teachers, post-graduate students, students of educational institutions and experts in transport enterprises for improving production efficiency.